Reducing background cytokine expression in epithelial cells without serum starvation - H. Antypas; B. Libberton; K. Melican (MethodsX, 2014)
Cellular excretion of inflammatory cytokines is an important experimental read-out in a wide range of molecular biology fields. The addition of serum to growth media provides the optimal growing conditions for most cell types. When studying the effect of bacteria and bacterial products on these cells serum starvation is often performed as a standard procedure [1] to avoid unwanted stimulation by the serum components. The full effect of serum starvation on cell behaviour and inflammatory responses is unknown, though it has been suggested to induce various responses that can interfere with experimental results and conclusions [2]. Serum starvation has been shown to cause cells to undergo apoptosis and autophagy [3,4] as well as superoxide production and increasing cell susceptible to inflammatory stimuli [5]. In order to study stimulation of healthy epithelial cells, a new approach was required that limited unwanted stimulation but supported normal cell growth. Analysis of different serum preparations on the background cytokine expression of renal epithelial cells demonstrated conditions in which the background cytokine expression can be reduced without the need to serum starve the cells. Endotoxin content was not found to be the most relevant factor in inducing an inflammatory response in epithelial cells. Charcoal stripped preparations of foetal bovine serum (FBS) produced the lowest background expression of IL-6 and IL-8 without the need for serum starvation. • Selection of the serum source allows for cytokine expression experiments to be performed without serum starvation. • Charcoal stripped preparations of FBS produces the lowest background cytokine expression without serum starvation. • Serum factors other than endotoxin content influence cytokine secretion.